Das englische Geschäft mit der Nachtigall : Betrachtungen zum italienischen Opernwesen im London des 19 - Zechner, Ingeborg (2017)
This books deals with the Italian opera business in nineteenth century-London. A special emphasis lies on the opera singers as the most important protagonists of the London system. This special role will be examined through the analysis of the opera audience in London, the contractual practice and the tradition of the adaptation of operas to the likes of the London market as well as the substitution of arias.Die Publikation beschäftigt sich mit dem italienischen Opernwesen im London des 19. Jahrhunderts. Im Vordergrund stehen die Sänger als tragende Protagonisten des Londoner Opernsystems. Deren Bedeutung für den Londoner Opernmarkt wird mithilfe einer Analyse des Londoner Opernpublikums, der Vertragspraxis der Zeit und der Adaptions- und Einlagearienpraxis festgemacht...